2019
DOI: 10.1016/j.cities.2019.102408
|View full text |Cite
|
Sign up to set email alerts
|

Does exposure to richer and poorer neighborhoods influence wellbeing?

Abstract: Geographical differences in wellbeing have attracted increased attention in the science of happiness literature and recent research has become particularly interested in highresolution spatial differentiation within cities. This study contributes to this literature by analyzing the relationships between subjective wellbeing and relative income at the neighborhood level using activity-travel survey data from 2010 in Hong Kong. In contrast to previous studies, the analysis concentrates not only on life satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 73 publications
(94 reference statements)
0
14
0
4
Order By: Relevance
“…Additionally, future researchers could extend the current findings by exploring how the perceived gap between low‐ and high‐SES groups within a society could influence meta‐dehumanization and perceived well‐being. Previous research indicated that well‐being could be influenced by the perceived (up or down) social comparisons within a given neighbourhood (Wang, Schwanen, & Mao, 2019). Thus, it might be expected that meta‐dehumanization and well‐being will worsen for low‐SES groups when, in their daily life, they are confronted in different contexts (e.g., jobs, schools, residential areas) with higher SES groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, future researchers could extend the current findings by exploring how the perceived gap between low‐ and high‐SES groups within a society could influence meta‐dehumanization and perceived well‐being. Previous research indicated that well‐being could be influenced by the perceived (up or down) social comparisons within a given neighbourhood (Wang, Schwanen, & Mao, 2019). Thus, it might be expected that meta‐dehumanization and well‐being will worsen for low‐SES groups when, in their daily life, they are confronted in different contexts (e.g., jobs, schools, residential areas) with higher SES groups.…”
Section: Discussionmentioning
confidence: 99%
“…As a well-researched topic that covers distinct disadvantaged social groups (e.g., ethnic minorities and low-income residents), socio-spatial segregation has long been understood as spatial separation or isolation of residential locations [25][26][27][28]. In recent decades, there has been a rise of scholarly interest in framing socio-spatial segregation in terms of locations where individuals conduct everyday activities, and thus have opportunities to encounter other social groups, based on the assumption that such encounters are conducive to higher levels of inter-group interactions [12][13][14][15]29]. Several recent studies not only provided strong evidence that the NEAP exists when examining mobility-dependent exposure but also showed that different social groups may be associated with different levels of the NEAP [6][7][8][9][10].…”
Section: Activity-based Segregation and Exposurementioning
confidence: 99%
“…Activity-travel diaries and GPS tracking can provide useful insight about the trips and non-movement of individuals whose relationships with the referent-we are ambiguous and potentially shifting, depending on where they are at particular times. These data can be complemented by interviews configured around them (as in Andrade et al's [2019] study of sex workers in Tijuana and Ciudad Juárez, Mexico), by data on biomarkers such as skin conductance or brain activity using devices that are worn on diary/tracking days, or by pre-existing data on who is present or lives in the places and territories that the research participants move through (as in Wang et al, 2019).…”
Section: Making Graspable: Focus On Liminal Subjectsmentioning
confidence: 99%